A synchrotron X-ray spectroscopy study of titanium co-ordination in explosive melt glass derived from the trinity nuclear test. Issue 23 (26th April 2019) - Bailey, D. J.; Stennett, M. C.; Ravel, B.; Crean, D. E.; Hyatt, N. C.
Abstract : This work presents the first determination of Ti speciation and co-ordination in trinitite via the use of X-ray absorption spectroscopy. Abstract : The speciation of Ti in trinitite, the explosive melt glass derived from the Trinity Test of 16 th of July 1945, was investigated by X-ray absorption spectroscopy (XAS). Ti K-edge XANES showed that Ti was present in the Ti(iv ) oxidation state for all samples. Fitting of pre-edge features by Gaussian functions and comparison with standards of known Ti coordination revealed significant variation in Ti coordination environment between samples. The variation of Ti coordination may be attributed to several factors including specific local chemistry and thermal histories of samples, in keeping with the highly heterogeneous microstructure of trinitite and the arkosic sand source material.